Ø´Ø±ÙˆØ· ØµØØ© ØµÙ„Ø§Ø© Ø§Ù„Ø¬Ù…Ø¹Ø© Ø¹Ù†Ø¯ Ø§Ù„Ø´Ø§ÙØ¹ÙŠØ© ÙˆØ§Ù„ØÙ†Ø§Ø¨Ù„Ø©ØŒ Ø¯Ø±Ø§Ø³Ø© Ù…Ù‚Ø§Ø±Ù†Ø© - Muhammad Yusram; Ariesman, Ariesman; Jefri, Jefri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to determine the opinions of scholars of the Shafii and Hambali schools regarding the legal requirements for Friday prayers and the legal implications of these differences of opinion. This study uses a deductive and inductive method with a comparative approach. The results of this study indicate that: (1) the conditions for the validity of Friday prayers according to the scholars of the Shafi'i school are the entry of time (after the sun has slipped), carried out in residential areas according to residents' habits, there are forty people who are subject to the obligation of Friday prayers, preceded by two sermons that separated between the two by sitting down, not preceded by another Friday prayer and no Friday prayer being performed at the same time except in a big city and the condition of the people being so large that it is difficult for them to gather (in one place) so that the Friday prayer may be performed in different areas at the same time. While the legal requirements for Friday prayers according to Hanbali scholars are that they may be carried out before the entry of Zuhur time and should be carried out after the entry of Zuhur time, carried out in residential areas according to the habits of the residents, the presence of forty, fifty or thirty congregations (there are mistakes), sermons, as for sitting between two sermons, the law is sunnah and the sermon remains valid without sitting; (2) the legal implication of the difference of opinion between the two schools of thought is that it can affect the legal validity of Friday prayers, namely if there are conditions that are not fulfilled in one of the schools, while these conditions have been fulfilled in other schools.